Designing and fabricating composites of PNIPAM@Au nanorods with tunable plasmon coupling for highly sensitive SERS detection. (April 2016) - Wu, Yiping; Li, Pan; Yang, Benhong; Tang, Xianghu
Graphical abstract: Highlights: Composites of PNIPAM@Au nanorods with tunable hot spots were synthesized. The tunable optical properties of the composite make they match more the laser of near-infrared-excitation. The limit of detection (LOD) for Thiram on the substrate is 10 −9  M. It is hoped the substrate could be applied in portal Raman instrument with the laser of 785 nm. Abstract: In this study, hybrid substrates composed of poly( N -isopropylacrylamide) hydrogels and Au nanorods (PNIPAM@AuNRs) that exhibit tunable plasmon coupling are designed and fabricated. In this process, Au NRs are deposited on the surface of a PNIPAM hydrogel, and the temperature is increased, causing the hydrogel template to shrink, thereby driving the Au NRs closer to each other. The resulting surface plasmon resonances (SPR) of the composite are observed as a large red-shift. The formation of more hot spots increases the already high sensitivity of surface-enhanced Raman scattering (SERS) detection, and the tunable optical properties enable closer matching of the laser to the near-infrared excitation required. Moreover, these hybrid substrates can be conveniently identified by optical microscopy, enabling in situ SERS detection with high sensitivity and reproducibility.